Seismic potential in and around the Sichuan basin from the dense GNSS network - Xu, Rui; Chen, Cong; He, Fuxiu; Liu, Xuemei (Frontiers in Earth Science, 2024)
The Sichuan basin (SCB) is situated at the southeastern edge of the Tibetan Plateau where widespread seismicity has occurred. In the past decades, seismic events occurred in and around SCB have been responsible for more than 100 thousand casualties. To quantify the present-day seismic hazard of this region, especially the densely populated Chengdu-Chongqing economic zone (CCEZ), we develop a probabilistic earthquake forecast model using strain rates derived from 187 Global Navigation Satellite System (GNSS) horizontal velocities, of which 102 velocity vectors are first released. The second invariant of the strain rate tensor suggests that the Shimian County and its surroundings are exposed to the highest seismic hazard in and around SCB. The second most dangerous area is located between 103–105°E. The Chongqing area is the least dangerous. The principal strain rate axes interior of the Sichuan basin suggest that this region is experiencing broad-scale extension, which according to our knowledge, is first revealed by our dense GNSS network. The comparison between the cumulative histograms of the second invariant of geodetic strain rate and earthquake count indicates that the geodetic strain rates in this region can serve as a reliable predictor of M≥6 earthquake locations. Thus, we proceed to calculate the total seismic moment anticipated for the entire area within the next 30 years.